Pemikiran Politik Thomas Hobbes Dalam Serial Drama Squid Game - Elyta Elyta; Hertanto Hertanto (Mahesa Research Center, 2022)
In 2021, South Korea will make the Squid Game drama series with the mystery horror genre. The research will look at the political thinking of Thomas Hobbes in this series with the aim of analyzing the form of natural consciousness, social contract in the form of the State which is broadcast through storylines, dialogues and descriptions of the situation in the Korean drama series Squid Game. This article is a literature study on the state of nature, social contract and the concept of the state from Thomas Hobbes' political thought through the drama series Squid Game produced from South Korea. His opinion of the state is scary, cruel, and obeyed like Leviathan to make the disorderly state of human nature controllable. Human nature is homo homini lupus or humans are wolves to each other. The social contract according to Thomas Hobbes is an agreement between the people and the state, but the state is not bound by the social contract. The state/king position is above the social contract, the state has absolute authority or is called the king, it cannot be wrong. This study concludes that in the Korean drama series Squad Game, there is a thought by Thomas Hobbes which states the importance of absolute state power to create perfection. Peace can be obtained by presenting fear to the individual through the State, conflict will be avoided, society will be subject to the law with fear that is continuously maintained by the State.